Therapeutic alternative for oral lichen planus treatment in an unusual location: case report - Dutra, Thaís Torres Barros; Bezerra, Thâmara Manoela Marinho; Chaves, Filipe Nobre; Feitosa, Sthefane Gomes; Costa, Fábio Wildson Gurgel; Pereira, Karuza Maria Alves (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Oral Lichen Planus (OLP) is considered a potentially malignant lesion (PML), although its rate of transformation is controversial. New treatments have been introduced recently, for example calcipotriene (D3 vitamin analog). Its incremental action with glucocorticoids is observed and isolated lip lesions may respond positively to combined topical therapy. Thus, objective of this case report is to show a therapeutic alternative for isolated and persistent OLP lip lesions. An 18-year-old teenager was referred to evaluate an erythematous lower lip lesion with approximately 10 years of evolution. The inspection revealed multiple erythematous areas surrounded by thin whitish streaks located in the vermilion of the lower lip. No abnormalities in the skin, nails, scalp or other areas of oral mucosa were observed. The incisional biopsy was performed and the microscopic exam showed areas of basal layer degeneration with intense mononuclear inflammatory infiltrate banded and predominantly subepithelial. The therapeutic proposal was topical application of Daivobet®, a combination of topical corticosteroids and vitamin D derivative. The lesion had remission after the fifteen days, medication was suspended and indicated when there was a relapse. During follow-up, no recurrences or complications were observed. That combination therapy may be a new approach in treating OLP.